Isolation and characterization of Pasteurella haemolytica from a field outbreak in sheep of Rajasthan - MISHRA, N; MISHRA, S; PAWAIYA, R V S; K BHAGWAN, P S (The Indian Journal of Animal Sciences, 2013)
An outbreak of pneumonia in sheep flocks of Tonk district of Rajasthan was investigated. The morbidity rate was 50%, mortality rate was 16% and hoggets were most affected. Pasteurella haemolytica was isolated from the lungs of morbid sheep and identified on the basis of cultural and biochemical characters. Biotype A was assigned on the basis of sugar fermentation reactions. The capsular antigen of the isolate was prepared by sodium chloride extraction procedure. The hyperimmune serum against the capsular antigen was raised in sheep. The antibody titre was 1: 4 in agar gel immunodiffusIon test. The sodium dodecyl sulphate polyacrylamide gel electrophoresis of the capsular antigen showed presence of 10 polypeptides of molecular weight 14kd to 205kd. The protein profile of the capsular antigen prepared from broth and solid media was similar. The characterization of outbreak strain confirmed the involvement of P. haemolytica.